Identification of Wheat Flour Segmentation Based on Household Consumer's Preferences - Ivonny Erlandharosi; Wahyu Supartono; Didik Purwadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
The aim of this study research was to indentify wheat flour segmentation based on household consumer. Samples of this research were CK, KB and SB. The research method was